The Influence of Social Media in the Digital Age on the Lives of Mothers and Teenager - Po,oe, Ony Resita; Syobah, Sy. Nurul; Beta, A. Rivai (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to explore the impact of social media use on the lives of mothers and adolescents in the digital era. Through a qualitative approach using interviews, observations, and questionnaires, this study found that social media such as Instagram and TikTok play a significant role in shaping communication patterns, self-expression, and household economic activities. For mothers, social media opens up opportunities to run online businesses and improve family welfare. Meanwhile, for teenagers, social media is a space for identity exploration, but also has the potential to cause psychological problems such as anxiety, sleep disturbances, and decreased self-confidence. The results show that family interactions are shifting as the intensity of technology use increases, which creates new challenges in the relationship between mothers and children. Low digital literacy among parents, as well as the lack of effective supervision strategies, increases the risk of exposure to negative content among adolescents. Therefore, it is important to develop adaptive and collaborative digital parenting approaches. This study concludes that digital literacy and media etiquette are key in optimizing the benefits of digital technology while minimizing its negative impacts. Collaboration between families, schools and communities is needed to form a generation that is resilient, critical and wise in facing the dynamics of digital life.